German-Iowan Strategies in Celebrating the Centennial of Alexander von Humboldt’s Birth - Roba, Bill (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2014)
The two largest cities of Eastern Iowa on the shore of the Mississippi River are Dubuque and Davenport. In each city, an elite group of German-Iowan leaders emerged by the late 1850s. Bill Roba describes and examines their strategies in celebrating the Centennial of Alexander von Humboldt’s Birth.